DESIMINASI PEMBERIAN TANDA PADA TERNAK SAPI POTONG DI DESA LIANG KECAMATAN SALAHUTU MALUKU TENGAH - Joseph, Godlief (Universitas Pattimura, 2024)
Cattle farming in rural areas is often considered a form of investment or living savings. Farmers maintain cattle as assets that can be sold at any time when they need urgent funds, such as for healthcare, education, or other expenses. Liang Village, located in Salahutu District, Central Maluku, has great potential for the development of beef cattle farming. However, its productivity remains low, partly due to a lack of proper livestock management. One important aspect of livestock management is individual identification. Without proper identification, it is difficult for farmers to track the growth of livestock, control diseases, and increase the market value of the cattle. This community service activity aims to raise awareness among farmers in Liang Village about the importance of livestock identification and technical assistance in the implementation of appropriate tagging methods. The desired outcome is that farmers will be able to manage their operations more effectively, especially in terms of livestock identification systems. Farmers have responded positively, as they view this as a beneficial and innovative approach. It is recommended that ongoing support be provided in the form of training on cattle tagging so that farmers can effectively monitor their livestock.